On Refined Neutrosophic Matrices and Their Application in Refined Neutrosophic Algebraic Equations - Mohammad Abobala (Journal of Mathematics)
The objective of this paper is to introduce the concept of refined neutrosophic matrices as matrices such as multiplication, addition, and ring property. Also, it determines the necessary and sufficient condition for the invertibility of these matrices with respect to multiplication. On the contrary, nilpotency and idempotency properties will be discussed.